The Effect of Product Quality and Brand Image on Xiaomi Smartphone Purchase Decisions - Yollanda Ayu Saputri; Supriyono (Indonesian Journal of Business Analytics, 2023)
This study aims to determine the effect of product quality and brand image on purchasing decision Xiaomi smartphone. The population in this study are Xiaomi smartphone consumers in the region of Rungkut Surabaya. The sampling method use is non-probability so that results obtained were 80 respondents. The measurement scale used in this studies is the Skala Likert scale. The data used is primary data, namely questionnaire data from answers to respondents and secondary data, namely data obtained from sales data and supporting sources for the research topic. The analysis used is partial least square (PLS)with validity test, reliability test, and hypothesis test. The result of the study, it was found that product quality and brand image has a positive and significant on purchasing decision smartphone Xiaomi.